2006
DOI: 10.1136/ard.2005.045237
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A5 polymorphism (−1C→T) and the presence of anti-annexin A5 antibodies in the antiphospholipid syndrome

Abstract: Background: Annexin A5 is thought to have a role in the pathophysiology of the antiphospholipid syndrome (APS)-a syndrome characterised by recurrent thrombosis and pregnancy morbidity. Objective: To investigate whether anti-annexin A5 immunoglobulin (Ig)M or IgG antibodies, or the 21CRT polymorphism of annexin A5, is a risk factor for thrombosis or miscarriage, and whether the 21CRT polymorphism is correlated with APS. Methods: A cohort study was carried out with a population of 198 patients with primary APS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…Actually, other studies reported an association of antiannexin antibodies with peculiar autoimmune conditions, such as discoid lupus 25 and antiphospholipid syndrome, typically a serious condition potentially causing vascular events. [26][27][28] Therefore, our results go in the direction of other reports that already suggested a generic implication of antihistones, anti-DNA, and antipodocyte antibodies. 11,29,30 Looking at the renal composition of autoantibodies, a relevant finding here is the preponderance in glomeruli of antibodies of the IgG2 isotype (anti-a-enolase/annexin AI and H3 histone) with little amounts of anti-DNA IgG3 and predominant colocalization of anti-IgG4 with C1q in subepithelial deposits of class V biopsies.…”
Section: Discussionsupporting
confidence: 73%
“…Actually, other studies reported an association of antiannexin antibodies with peculiar autoimmune conditions, such as discoid lupus 25 and antiphospholipid syndrome, typically a serious condition potentially causing vascular events. [26][27][28] Therefore, our results go in the direction of other reports that already suggested a generic implication of antihistones, anti-DNA, and antipodocyte antibodies. 11,29,30 Looking at the renal composition of autoantibodies, a relevant finding here is the preponderance in glomeruli of antibodies of the IgG2 isotype (anti-a-enolase/annexin AI and H3 histone) with little amounts of anti-DNA IgG3 and predominant colocalization of anti-IgG4 with C1q in subepithelial deposits of class V biopsies.…”
Section: Discussionsupporting
confidence: 73%
“…Other investigators have not found enough data to support the diagnostic role of these antibodies [22][23][24][25]33,39]. The discrepancies among these studies are mainly due to the different diagnostic criteria used, the different disease stages and the different methods of determination of a-A5 [41].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, in this study the only significant risk factor for fetal loss in these patients were a-A5. On the other hand, de Laat et al [33] share the contrary opinion that a-A5 are not a risk factor for thrombosis or a pregnancy loss in patients with APS and SLE but the mutations in the A5 gene are an independent risk factor for thromboses and fetal loss, apart from the APS.…”
Section: Significance Of the Determination Of A-a5 In Patients With Smentioning
confidence: 88%
“…Many cross-sectional studies have been reported on associations between polymorphism and RPL, such as 4G/4G for plasminogen activator inhibitor-1 polymorphisms (OR 11.0, 95% CI 2.3-52.4), protein Z intron F G79A polymorphism (OR 0.3, 95% CI 0.1-0.8) and Annexin A5's -1C/T (OR 2.7, 95% CI 1.0-6.7) [27][28][29]. However, the clinical significance could not be established because most were not cohort studies.…”
Section: Discussionmentioning
confidence: 99%